Assessing microplastic as a vector for chemical entry into fish larvae using a novel tube-feeding approach. (February 2021) - Norland, Sissel; Vorkamp, Katrin; Bogevik, André S.; Koelmans, Albert A.; Diepens, Noël J.; Burgerhout, Erik; Hansen, Øyvind J.; Puvanendran, Velmurugu; Rønnestad, Ivar
Abstract: A tube-feeding model for administering microplastic (MP, Ø = 30 μm) spheres to fish larvae was employed to quantify the uptake of hydrophobic organic contaminants (HOCs) into the larval body through a single administration of MP. Polychlorinated biphenyl-153 (PCB-153) was used as a representative HOC that can be sorbed to MP in the sea. Atlantic herring ( Clupea harengus ) larvae (34–51 days post-hatching) were selected as the animal model. The herring larvae were tube-fed a single load of up to 200 polystyrene or polyethylene MP spheres spiked with 14 C-labelled PCB-153, and the control larvae were tube-fed an isotonic solution without MP. At the time of sampling (24 h post feeding), some larvae had evacuated all MP spheres from the gut, while others still had MP remaining in the gut. In larvae with a significant number of MP spheres still present in the gut, whole-body scintillation counting (including the MP in the gut lumen) showed elevated levels of the tracer compared to those in the control fish larvae. For larvae in which all or almost all MP had been evacuated by the time of sampling, the tracer levels of the whole body were not significantly different compared to those for the control fish larvae. These data indicate that there was no significant transfer of PCB-153 from contaminated MP into fish larvae within a gut-transit time of <24 h. This study suggests that the vector role of MP in HOC uptake and absorption may be minor compared to that of other HOC uptake pathways. Highlights: Microplastic (MP) spheres loaded with PCB-153 were tube-fed to Atlantic herring. Fish larvae gut transit time is typically less than 24h. There was no transfer of PCB-153 from MP into the larval body. This is a novel approach to study absorption from contaminated MP into fish larvae.